PENGARUH PEMBERIAN URINE SAPI DAN PUPUK NPK TERHADAP KOMPONEN PRODUKSI TANAMAN JAGUNG MANIS(Zea mayssaccharata Sturt)DI LAHAN GAMBUT - Kiki ' Sanjaya; Jurnawaty ' Sjofjan; Nurbaiti ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed to determine the effect of cow urine and NPK fertilizers, as well as getting the best dose on production component of sweet corn on peatlands. The research was conducted on peat types sapric in Experimental Farm, Faculty of Agriculture Rimbo Panjang TambangDistrict of Kampar Regency and conducted over three months starting in December 2015 to March 2016. The study was conducted using a factorial RAL consisting of two factors with the first factor is giving of cow urine U1: cow urine concentration of 150 ml/l, U2: cow urine concentration of 300 ml/l, U3: cow urine concentration of 450 ml/l and U4: cow urine concentration of 600 ml/l. The second factor is the NPK fertilizer is P0: without fertilizer NPK, P1: award NPK 150 kg/ha and P2: award NPK 300 kg/ha. Data were analyzed statistically using analysis of variance followed by Duncan's multiple range test at 5% level. Parameters measured were plant growth rate, production per plot, weight per cob without husk, cob without husk lengthand diameter cob without husk.The results showed interaction NPK fertilizer of cow urine and cow urine as well as single factor effect is not real to each parameter of observation. Giving a single factor NPK showed an increased rate of plant growth, production per plot, weight per cob without husk, without husk cob lengthand cob diameter without husk. Increased production of sweet corn is highest at a dose of 300 ml of cow urine treatment with NPK fertilizer 150 kg/ha of 6,53 kg/5,25 m2 (equivalent to 5,0 tons/ha), increased 83% compared with no fertilizer NPK and 150 ml cow urine. Keyword: Cow urine, NPK fertilizer and sweet corn